Analisis Mutu Pelayanan dengan Kepuasan Pasien Rawat Jalan di UPT Puskesmas Sangatta Utara (Studi : Potong Lintang) - Noriah, Noriah; Adrianto, Ratno; Ramdan, Iwan Muhamad (Jurnal Epidemiologi Kesehatan Komunitas, 2025)
Background: Health service quality reflects how well services meet patient satisfaction as it affects patient trust and adherence while also demonstrating the accountability of primary health care facilities. This study aims to examine the impact of service quality on outpatient satisfaction at UPT Puskesmas Sangatta Utara.Methods: This study utilized an analytical survey with a cross-sectional design. The population included community members seeking care at the North Sangatta Health Centre. A total of 271 respondents were selected based on the Lemeshow formula, using purposive sampling as the sampling method. Data were collected through a structured questionnaire that included demographic characteristics and research variables. Data analysis was conducted using a combination of univariate, Chi-square, and multiple logistic regression methods to explore the relationships and effects among the variables.Result: The results showed that variables significantly associated with outpatient satisfaction were technical competence, facility accessibility, service effectiveness, continuity, safety, comfort, information, timeliness, and interpersonal relations (p < 0.05). Service efficiency was not significantly associated with patient satisfaction (p > 0.05). The most influential factor was interpersonal relations, with the highest odds ratio of 2.294 (95% CI: 1.381–3.809).Conclusion : This study demonstrated that outpatient satisfaction at the North Sangatta Health Centre was influenced by multiple service aspects, with interpersonal relations emerging as the most dominant factor. These findings emphasized the importance of improving healthcare workers’ communication and interaction with patients to enhance overall satisfaction.